Chemistry E-Module Based on Socio Scientific Issues (SSI) for Reaction Rate Material to Increase Senior High School Students' Chemical Literacy - Rizki Novitasari; Joko Waluyo; Nuriman Nuriman (Green Publisher Indonesia, 2022)
Learning chemistry contributes to chemical literacy in specific and science literacy in general. Chemical literacy relates to the ability to think scientifically by using chemical knowledge and natural phenomena identification. Chemical literacy is defined as the ability to understand and implement chemistry knowledge in everyday life by comprehending three aspects comprising: knowledge, awareness and chemistry implementation in everyday life accurately and effectively. Based on the result of the questionnaire which has been distributed to chemistry teachers in Jember regency through chemistry MGMP, it shows that 71,8% of chemistry teachers stated that students’ chemical literacy skill in learning did not meet the target. Chemical literacy has significant relation to the Socio-Scientific Issues (SSI) drown as social problem by using scientific context. This problem considered as scientific issue developed in society. Then, this problem is analyzed further in rate reaction materials. This research used quasi-pretest-posttest experiment without using control class. To analyze the data, this research used both quantitative and qualitative methodologies. The sample in this research consisted of 36 senior high school students in Senior High School of Ambulu grade XI MIPA 6. The result of this research based on both pretest and posttest using open ended questions showed that there was significant improvement on students’ chemical literacy. Therefore, it was in high category 0,71